PELESTARIAN DIKIA RABANO DI NAGARI KOTO RAJO KABUPATEN PASAMAN 1987-2022 - Nur Azizah; Erniwati Erniwati (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research discusses the characteristics and efforts to preserve Dikia Rabano Art in Nagari Koto Rajo, Pasaman Regency, 1987-2022. This research aims to analyze the steps that have been taken to maintain the continuity of Dikia Rabano in Nagari Koto Rajo, Pasaman Regency. Using four techniques in historical research, namely heuristics, is the first step in searching for historical sources, followed by sources criticism, interpretation and historiography. This research was motivated by the lack of public interest in studying Dikia Rabano resulting in various conservation efforts carried out by the community and full support from the government. The result of this research show that the characteristics of Dikia Rabano in Nagari Koto Rajo are always performed in traditional processions  such as weddings, naming children and thanksgiving for the hajj. Efforts to preserve Dikia Rabano were carried out throught several forms of efforts, namely protection, development and utilization, starting from  1987 to 2022. At the protection stage, there were active efforts from the community and government to maintain and protect Dikia Rabano, the next stage, namely development, at this stage was supported by several steps conservation efforts such as maintenance, training and display. Finally, Dikia Rabano’s art contains many useful educational values that can increase insight and knowledge. So it can be concluded that Dikia Rabano is still sustainable today thaks to conservation efforts carried out bg the community and government. Dikia Rabano managed to survive and thrive.